Stimulated X-ray Raman scattering – a critical assessment of the building block of nonlinear X-ray spectroscopy. (22nd September 2016) - Kimberg, Victor; Sanchez-Gonzalez, Alvaro; Mercadier, Laurent; Weninger, Clemens; Lutman, Alberto; Ratner, Daniel; Coffee, Ryan; Bucher, Maximilian; Mucke, Melanie; Agåker, Marcus; Såthe, Conny; Bostedt, Christoph; et al.
Abstract : With the invention of femtosecond X-ray free-electron lasers (XFELs), studies of light-induced chemical reaction dynamics and structural dynamics reach a new era, allowing for time-resolved X-ray diffraction and spectroscopy. To ultimately probe coherent electron and nuclear dynamics on their natural time and length scales, coherent nonlinear X-ray spectroscopy schemes have been proposed. In this contribution, we want to critically assess the experimental realisation of nonlinear X-ray spectroscopy at current-day XFEL sources, by presenting first experimental attempts to demonstrate stimulated resonant X-ray Raman scattering in molecular gas targets.